Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1097/00006534-200101000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Submucous Cleft Palate: A Comparative Trial of Two Modalities for Palatal Closure

Abstract: Submucous cleft palate is a congenital malformation with specific clinical and anatomical features. It can be present with or without velopharyngeal insufficiency. Surgical treatment of this malformation is indicated only when velopharyngeal insufficiency has been demonstrated. This article compares two modalities of surgical treatment for submucous cleft palate. The first includes a minimal incision palatopharyngoplasty, as described in a previous report. The second combines the first technique with additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 17 publications
1
46
0
7
Order By: Relevance
“…Patients often present after speech has already developed, with abnormal speech as the major complaint. Unfortunately, due to the delayed presentation, surgical repair of the submucous cleft palate does not correct speech (6). Early diagnosis and identification of the types of submucous cleft palate that will lead to a speech abnormality before speech development is the key to successful management of these patients.…”
mentioning
confidence: 99%
“…Patients often present after speech has already developed, with abnormal speech as the major complaint. Unfortunately, due to the delayed presentation, surgical repair of the submucous cleft palate does not correct speech (6). Early diagnosis and identification of the types of submucous cleft palate that will lead to a speech abnormality before speech development is the key to successful management of these patients.…”
mentioning
confidence: 99%
“…The diagnosis of a submucous cleft palate may be difficult, especially for inexperienced clinicians. Since the description of submucous cleft palate with the classic triad by Calnan [8][9][10], several reports have demonstrated that there are a number of cases of submucous cleft palate without bifid uvula and/or muscular diastasis of the velum [3,9,10]. It is also of vital importance to perform a careful palpation of the palate in order to detect a notch on the posterior border of the hard palate, which may be the only sign of a submucous cleft palate.…”
Section: Cleft Palate and Submucous Cleft Palatementioning
confidence: 99%
“…Moreover, the diagnosis may have to be endoscopic in some cases. It is not until a detailed video nasopharyngoscopy detects hypoplasia or agenesia of the musculus uvulae that a definite diagnosis can be made [10]. The use of the terms submucous cleft palate and "occult" submucous cleft palate have somehow created some confusion.…”
Section: Cleft Palate and Submucous Cleft Palatementioning
confidence: 99%
“…Há muitos anos tem-se investigado os efeitos da cirurgia sobre a fala e a respiração utilizando julgamento perceptivo associado ou não a métodos objetivos (10)(11)(12)(13)(14)(15)(16)(17)28,29) . As repercussões do retalho faríngeo têm sido objeto de estudo, também, no Laboratório de Fisiologia do HRAC-USP (4,6,21,22) .…”
Section: Figuraunclassified
“…Os dois orifícios posicionados lateralmente ao retalho devem ter diâmetro e permeabilidade suficientes para permitir a respiração nasal em repouso (9) . Muitos estudos relataram a efetividade do retalho farín-geo na redução dos sintomas da fala (4,6,(10)(11)(12)(13)(14)(15)(16)(17)(18) . Por outro lado, o retalho faríngeo está associado a um potencial e significante de comprometimento das vias aéreas superiores, incluindo-se entre esses comprometimentos desde a hiponasalidade, obstrução nasal crônica, até ronco e apnéia obstrutiva do sono, que podem trazer consequências graves aos pacientes (4,10,(19)(20)(21) .…”
Section: Introductionunclassified